PROSPEK INDUSTRI MARGARIN ALPOKAT SKALA INDUSTRI RUMAH TANGGA - Wahyu Mushollaeni (BUANA SAINS, 2011)
Avocados had a fairly complete nutrient content and the price was quite affordable, so that the processing of avocados worth to be developed. Fruit not only on consumption in fresh condition, but with additional processing in order to get a new flavor or to get varied diet and to get the benefits of the avocado fruit. To cope with the abundance of the product during the main harvest, it would require further processing, so that the economic value of the avocado fruit does not fall. Both of the processing to extend the shelf life and processing for product diversification. Avocado in an optimal utilization has not been done, then to overcome, given an alternative form of avocado fruit processing, thereby increasing the range of dishes, namely margarine avocado. Hopefully with a new product in the form of margarine avocado, can increase the economic value of the avocado. In addition, more durable and can be used repeatedly without reducing flavor. This study aims to determine the feasibility of the process and financially household scale industries that produce margarine from avocado fruit. The results showed that at the household scale industries, the use of glycerin in margarine, avocados, can increase the value of consumer preferences, so that the margarine produced can be marketed properly. The use of glycerin was limited at concentrations of 10% for margarine and avocado consumers preferred feasible physically and chemically. Financially, the effort is worth the effort or established with a value of 16.37% IRR and NPV Rp. 4,435,371